Development of a test device for the evaluation of hydrodynamic lubrication in thrust bearings - Pasanen, Aapo; Kleemola, Jaakko; Lehtovaara, Arto (Tribologia - Finnish Journal of Tribology, 2008)
Oil lubricated thrust and journal bearings are widely used in industrial machines such as in stone crusher applications. In this study, a laboratory-scale test device for the evaluation of hydrodynamic lubrication in thrust bearings is developed. In the test device, the normal load, rotation speed, lubricant supply temperature and inlet flow rate can be adjusted and measured continuously and independently. In addition, thrust plate temperature and friction torque can be measured. This allowed initial testing of the functionality of the transient hydrodynamic model, which had been developed earlier to enhance bearing design and the testing process. The results show that the trends of the measured and the calculated results correspond well. The absolute friction coefficient values are also in reasonable agreement. The obvious main cause for deviation of results is the oil temperature in the pad inlet, exact estimation of which, by theoretical or experimental means, is complicated.